ANALYSIS OF THE STATEOF THE UKRAINIAN IT MARKET - STYSLO, TARAS; VASHCHYSHCHAK, SERHII; BOICHUK АNDRII; STYSLO, OKSANA; DOTSENKO, Y. (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Today, the global IT community is experiencing significant growth in digital production and software. Nearly 30 million software developers from around the world are working to meet the digital needs of the population. And this number is constantly growing. Many factors have led to an increase in digital production all over the world, namely: the transition of most trading platforms to online commerce, the introduction of online services in most countries, the digitalization of public services, the rapid growth and promotion of technologies related to the circulation and implementation of cryptocurrencies and block-chain, the rapid growth of digital technology in the medical field and much more. It is important to note that the growth of Ukrainian IT is significantly exceeding the global figure in terms of growth and has reached 26 percent since the beginning of this year. Given the rapid change in technology and market segmentation in accordance with the practical skills of certain technologies, universities often can’t adapt themselves to current market needs and train a sufficient number of specialists. The number of trained specialists is positively affected by internal courses being offered by leading Ukrainian and global companies. Often such programs are designed to train professionals who just begin their careers in the field, and for university graduates who lack practical experience in projects. Such programs are more concerned with preparation of specialists at the Trainee and Junior level, which is certainly important, but the main shortage of staff is being observed in the segment of specialists at the middle and higher level. Given the peculiarities of the domestic information technology market, it is sometimes difficult to find a specialist in accordance with the requirements of a vacancy, as the specifics of each company, technology and requirements for specialists are significantly different. At the present stage there is an actual issue of training of a potential candidate for the position by the employer and employee of his company at the Middle level and above.